Aging, diversity, and health: the Brazilian and the Canadian context - Lisiane Manganelli Girardi Paskulin (Acta Paulista de Enfermagem, 2011)
Aging is a universal and yet diverse phenomenon. This paper presents a review on the topic of diversity in the context of the aging populations in Brazil and Canada. The diversity of the aging population in both countries is discussed in terms of gender, ethnicity, age groups and living conditions while considering the impact on the health care systems. Understanding and reflecting on the Brazilian and Canadian realities reinforces the need for respecting these diversities when developing and implementing local health policies and interventions. There are some similarities regarding gender, but marked differences in immigration patterns, education and living arrangements. The heterogeneity in the aging process within each country and between them carries different expectations and generates social consequences that manifest themselves in differences in health situations, resulting in new challenges to health services and the formulation of public policies for this age group in both countries.